Integrin α6β4 signals through DNA damage response pathway to sensitize breast cancer cells to cisplatin - Chen, Min; Marrs, Brock; Qi, Lei; Knifley, Teresa; Weiss, Heidi L.; D’Orazio, John A.; O’Connor, Kathleen L. (Frontiers in Oncology, 2022)
Integrin α6β4 is highly expressed in triple negative breast cancer (TNBC) and drives its most aggressive traits; however, its impact on chemotherapeutic efficacy remains untested. We found that integrin α6β4 signaling promoted sensitivity to cisplatin and carboplatin but not to other chemotherapies tested. Mechanistic investigations revealed that integrin α6β4 stimulated the activation of ATM, p53, and 53BP1, which required the integrin β4 signaling domain. Genetic manipulation of gene expression demonstrated that mutant p53 cooperated with integrin α6β4 for cisplatin sensitivity and was necessary for downstream phosphorylation of 53BP1 and enhanced ATM activation. Additionally, we found that in response to cisplatin-induced DNA double strand break (DSB), integrin α6β4 suppressed the homologous recombination (HR) activity and enhanced non-homologous end joining (NHEJ) repair activity. Finally, we discovered that integrin α6β4 preferentially activated DNA-PK, facilitated DNA-PK-p53 and p53-53BP1 complex formation in response to cisplatin and required DNA-PK to enhance ATM, 53BP1 and p53 activation as well as cisplatin sensitivity. In summary, we discovered a novel function of integrin α6β4 in promoting cisplatin sensitivity in TNBC through DNA damage response pathway.